Cognitive Correlates of Hippocampal Atrophy and Ventricular Enlargement in Adults with or without Mild Cognitive Impairment - Naira Goukasian; Shai Porat; Anna Blanken; David Avila; Dimitar Zlatev; Sona Hurtz; Kristy S. Hwang; Jonathan Pierce; Shantanu H. Joshi; Ellen Woo; Liana G. Apostolova (Dementia and Geriatric Cognitive Disorders Extra, 2019)
We analyzed structural magnetic resonance imaging data from 58 cognitively normal and 101 mild cognitive impairment subjects. We used a general linear regression model to study the association between cognitive performance with hippocampal atrophy and ventricular enlargement using the radial distance method.Bilateral hippocampal atrophy was associated with baseline and longitudinal memory performance. Left hippocampal atrophy predicted longitudinal decline in visuospatial function. The multidomain ventricular analysis did not reveal any significant predictors.